Understanding Archimedes Law: What the Best Teaching Strategies for Vocational High School Students with Hearing Impairment - Saepul Hidayat, Deden; Rahmat, Cece; Fattah, Nanang; Rochyadi, Endang; Nandiyanto, Asep; Maryanti, Rina (Journal of Technical Education and Training, 2020)
The purpose of this study was to demonstrate strategies in teaching the Archimedes law in the concept of floating, hovering, and sinking using egg as a model to students with hearing impairment (SHI). This study used a single-subject design with pre-test and post-test. The subjects of this study were three students with SHI at the Bandung Vocational School, Indonesia. Teaching was delivered using several methods, in which we used and compared â€œconventional teaching methodâ€ and â€œcombination of conventional method and experimental demonstrationâ€. The conventional method was done by giving lectures, question and answer, and assignments. The experimental demonstration was carried out by doing experiment and observing the eggs that were sinking, hovering, and floating. The results showed that the conventional teaching method was ineffective. Students with SHI found it difficult to understand an abstract concept because they have problems in auditory perception. However, when combining experimental demonstration supported with media, the difficult subjects could be taught to students with SHI. The reason for achieving successful teaching was because the experimental demonstration method improved studentsâ€™ focus, helping students with SHI to easily understand the subject matter. This study also gives idea that the teacher must choose visual learning methods and media to make them as attractive as possible. Indeed, understanding the Archimedes law is important for students to understand advanced subjects related to the Archimedes law in vocational school.